Manuscript of the Qur'an of the Kasunan Palace of Surakarta (coded MAA.001): A Historical-Philological Study of Writing Errors and Their Implications for Interpretation - Ainur Rhain; Alfiyatul Azizah; Yeti Dahliana; Andri Nirwana AN; Ahmad Nurrohim; Riza Maulana; Mohamad Muhajir; Muhammad Arif Musa (ZAD Al-Mufassirin, 2026)
The manuscript of the mushaf al-Qur'an produced by the Surakarta Sultanate represents an intellectual heritage of Nusantara Islam possessing significant historical, philological, and cultural value. This research aims to identify the characteristics of the manuscript, examine the nature of the scribal anomalies contained within, and analyze its implications for the meaning and interpretation of the Qur'an. The research uses a qualitative method with a tahqiq approach of the manuscript combined with codicological analysis, paleography, and text comparison against the standard Ottoman rasm. The object of research is focused on the mushaf  manuscript of the mushaf coded MAA.001 which is stored in the Library of the Great Mosque of Kasunanan Surakarta. The results of the study show that the manuscript is estimated to have been written in the period 1780–1820 AD and functions as a liturgical, educational, and symbolic medium of religious legitimacy in the palace environment. The tahqiq analysis reveal several writing errors in the QS. al-Taubah verses 81, 83, and 84, in the form of changes in letters and harakat that cause a significant shift in meaning, but are not related to the variation of authentic qira'at. In addition, there was a tendency to use the rasm imlā'ī mixed with the rasm 'Utsmānī as well as orthographic inconsistencies in some parts of the manuscript. These findings show that the variation in writing is more caused by technical factors of copying and uneven standardization of mushaf in the archipelago than by differences in qira'at traditions. This study emphasizes the importance of tahqiq studies on the Nusantara mushaf manuscripts as an effort to maintain the accuracy of the Qur'an text, reconstruct the history of Islamic scientific transmission in Java, and support the preservation of the heritage of Indonesian Islamic manuscripts.